2011
DOI: 10.1596/1813-9450-5914
|View full text |Cite
|
Sign up to set email alerts
|

Investing across Borders with Heterogeneous Firms: Do FDI-Specific Regulations Matter?

Abstract: Using a new dataset, Investing Across Borders 2010, on selected regulations that govern foreign direct investment (FDI) in 87 countries, and direct investment they receive from 30 OECD source countries, this paper explores how much FDI-specic policies and institutions inuence FDI inows when rms are heterogeneous in terms of productivity. The analysis overhauls conventional estimation techniques by directly addressing biases resulting from country and rm selection. The paper nds evidence of substantial heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…However, our analysis and past research shows that there is no correlation between the size of the economy (measured by GDP) and the degree of openness as measured by the Investing Across Sectors indicators. There is a modest positive correlation between GDP per capital and sectoral openness, suggesting that higher-income economies tend to be more open to foreign investment across sectors, although this correlation is not statistically significant (Waglé, 2011). Many economies are in the process of letting go of restrictions in some sectors.…”
Section: Trendsmentioning
confidence: 92%
“…However, our analysis and past research shows that there is no correlation between the size of the economy (measured by GDP) and the degree of openness as measured by the Investing Across Sectors indicators. There is a modest positive correlation between GDP per capital and sectoral openness, suggesting that higher-income economies tend to be more open to foreign investment across sectors, although this correlation is not statistically significant (Waglé, 2011). Many economies are in the process of letting go of restrictions in some sectors.…”
Section: Trendsmentioning
confidence: 92%
“…Moreover, Waglé (2011) indicated that liberalisation generally pays for itself over time, because distorted economies can allocate resources effectively and efficiently in the long run, which contributes to economic growth by widening the tax base. Nevertheless, it is still important for African countries to note that the AfCFTA is not a magic formula that will instantaneously solve the socioeconomic challenges of the continent.…”
Section: Adjustment Costsmentioning
confidence: 99%
“…10 We expand on these results by including eleven more European countries, controlling for more country-and firm-level factors, and employing a resampling technique to ensure that the sample accurately reflects the population. Wagle (2010) investigates the effects of regulation on FDI and concludes that FDI-increasing regulations prompt beneficiary firms to grow more quickly, through either selection effects or knowledge transfers. 11 We test for these effects using business environment variables.…”
Section: Motivation and Related Literaturementioning
confidence: 99%
“…Theory and experience indicate that openness to foreign investment helped these economies generate employment, upgrade technology, and improve managerial knowledge to accelerate productivity growth. In this regard, business regulations play an important role in attracting FDI, even after controlling for market size and factor endowments (Wagle, 2010;Demekas et al, 2007).…”
Section: Figure 3 Fdi Flows Into Europe All Sectors 1985-2009mentioning
confidence: 99%